2022
DOI: 10.3389/fbioe.2022.866290
|View full text |Cite
|
Sign up to set email alerts
|

Can Manganese Dioxide Microspheres be Used as Intermediaries to Alleviate Intervertebral Disc Degeneration With Strengthening Drugs?

Abstract: Degenerative disc disease (DDD) is a pathological condition associated with intervertebral discs (IVDs) that causes chronic back pain. IVD degeneration has become a significant issue in contemporary society. To date, numerous biological therapies have been applied to alleviate the progression of DDD, among which therapeutic protein injection is the most direct and convenient. However, there are some limitations to applying direct protein injection therapy, the most significant being that the efficacy of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Varied regional, local, and institutional policies contribute to the potential absence of numerous clinical trials that have received approval from alternative regulatory bodies, such as the European Union Drug Regulating Authorities Clinical Trials Database, national boards, or local institutional review boards. Indeed, recent systematic reviews investigating the available clinical evidence on disc regeneration have included a significantly higher number of published studies in addition to the trials found in our search 4,65 . Therefore, although representative, the conclusions of this study may be partial and not completely faultless.…”
Section: Discussionmentioning
confidence: 80%
“…Varied regional, local, and institutional policies contribute to the potential absence of numerous clinical trials that have received approval from alternative regulatory bodies, such as the European Union Drug Regulating Authorities Clinical Trials Database, national boards, or local institutional review boards. Indeed, recent systematic reviews investigating the available clinical evidence on disc regeneration have included a significantly higher number of published studies in addition to the trials found in our search 4,65 . Therefore, although representative, the conclusions of this study may be partial and not completely faultless.…”
Section: Discussionmentioning
confidence: 80%
“…IL-1β is the most widely studied inflammatory factor in IVDD and is associated with inflammatory radiculopathy ( 13 ). IL-1β accelerates IVDD mainly by inducing the expression of MMPs in the ECM ( 35 , 97 ). This process primarily depends on wingless-related integration site (Wnt)/β-catenin signaling ( 98 ).…”
Section: Regulation Of the Inflammatory Microenvironmentmentioning
confidence: 99%